Labor, Capital, and Production in a Globalized World: A Reappraisal through Miroslav Volf's Theology of Work - Edi Purwanto; Frans H. M. Silalahi (Institut Kristen Teologi Real Batam, 2026)
This article offers a theological and ethical reappraisal of labor, capital, and production within the context of globalized economic systems through Miroslav Volf’s theology of work. Rather than treating labor merely as an economic input, the study interprets work as participation in God’s creative and redemptive activity through the empowering presence of the Holy Spirit. Employing a qualitative normative-theological approach, the article examines biblical teachings on work, justice, stewardship, and communal responsibility in dialogue with Volf’s concept of work in the Spirit. The study argues that globalization intensifies ethical distortions when labor is reduced to a commodity, capital is detached from moral accountability, and production is governed primarily by profit maximization. In response, Volf’s theology offers a constructive framework for understanding work as the expression of Spirit-given charisms that participate in God’s ongoing work of creation and new creation, capital as an instrument for human flourishing and responsible stewardship, and production as a moral practice oriented toward justice, solidarity, and the common good. The article concludes that churches, Christian professionals, and faith-based institutions should cultivate marketplace ministry, ethical entrepreneurship, and labor advocacy as concrete expressions of Spirit-empowered economic discipleship in contemporary society. Abstrak Artikel ini menawarkan telaah teologis dan etis terhadap relasi antara tenaga kerja, modal, dan produksi dalam konteks sistem ekonomi global melalui perspektif teologi kerja Miroslav Volf. Berbeda dari pendekatan ekonomi yang memandang tenaga kerja semata-mata sebagai faktor produksi, penelitian ini memahami kerja sebagai partisipasi manusia dalam karya penciptaan dan penebusan Allah melalui pemberdayaan Roh Kudus. Dengan menggunakan metode kualitatif normatif-teologis, penelitian ini mengkaji ajaran-ajaran Alkitab mengenai kerja, keadilan, penatalayanan, dan tanggung jawab komunal dalam dialog dengan konsep work in the Spirit yang dikembangkan oleh Volf. Hasil penelitian menunjukkan bahwa globalisasi memperdalam berbagai distorsi etis ketika tenaga kerja direduksi menjadi komoditas, modal dilepaskan dari tanggung jawab moral, dan produksi didominasi oleh orientasi maksimalisasi keuntungan. Sebagai respons terhadap kondisi tersebut, teologi Volf menawarkan suatu kerangka konstruktif yang memahami kerja sebagai perwujudan karunia-karunia Roh Kudus (Spirit-given charisms) yang memungkinkan manusia berpartisipasi dalam karya Allah yang terus berlangsung menuju penciptaan baru, memandang modal sebagai sarana bagi kesejahteraan manusia dan penatalayanan yang bertanggung jawab, serta menempatkan produksi sebagai praktik moral yang berorientasi pada keadilan, solidaritas, dan kesejahteraan bersama (common good). Penelitian ini menyimpulkan bahwa gereja, para profesional Kristen, dan berbagai institusi berbasis iman perlu mengembangkan pelayanan di marketplace, kewirausahaan yang beretika, serta advokasi bagi pekerja sebagai wujud nyata pemuridan ekonomi yang diberdayakan oleh Roh Kudus di tengah masyarakat kontemporer.